Pendekatan Customer Relationship Management (CRM) Big Hit Entertainment pada Global Fandom - Ratih Frayunita Sari (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2020)
Market research is important in business, furthermore, market research is considered a way of creating effective strategies and as a basis for consideration in marketing decision making. One of the goals in market research is always oriented towards creating relationships between corporate with customers or known as Customer Relationship Management (CRM). The CRM approach combines the policies, processes, and strategies that the company uses to interact with customers and also to track customer information. Related business, South Korea has become an influential country in the world because of the K-pop music business. Big Hit Entertainment which is the smallest agency in Korea has spawned the most phenomenal idol group idols are BTS to penetrate the international market especially the United States. Big Hit Entertainment is always consistent with various market research approaches CRM in particular. This paper will discuss how Big Hit Entertainment performs various Customer Relationship Management (CRM) strategies in increasing ARMY loyalty as a BTS fan and elaborating communication global marketing. The author will explain the conceptual approach related to CRM and its relationship to market research. Furthermore, the discussion will be classified in several sub-discussion. First, it will describe BTS as a product of Big Hit Entertainment's business. Second, discuss the market research approach of Big Hit Entertainment. Third, customer research through Membership Survey of BTS. Fourth, form of Big Hit Entertainment CRM approach. Fifth offers CRM development in Big Hit market review in the future.